Integrating Food Technology and Chemistry for Sustainable Fortification and Functional Food Development - Aptabani, Zidane Rakha (Professorline, 2025)
The growing demand for sustainable, nutritious, and health-promoting food has accelerated the integration of food chemistry and food technology in fortification and functional food development. This study presents a conceptual synthesis that explores how chemical mechanisms and technological processes can be harmonized to enhance nutrient bioavailability, product stability, and environmental sustainability. Relying on secondary data from peer-reviewed studies published between 2015 and 2025, the research identifies key intersections between molecular food chemistry, process optimization, and green food engineering. The analysis reveals that food chemistry provides the molecular foundation for understanding reactions such as oxidation, Maillard transformation, and enzymatic modification, which determine nutrient retention and sensory quality. Food technology operationalizes these reactions through controlled processing techniques such as microencapsulation, fermentation, and extrusion that preserve bioactive compounds and enable targeted nutrient delivery. Furthermore, the adoption of green chemistry principles, including the use of natural antioxidants, solvent replacement, and low-energy processing, supports the environmental dimension of sustainable production. The resulting conceptual framework, termed the Chemistry Technology Sustainability Nexus, demonstrates that integrating molecular precision with technological innovation can yield fortified and functional foods that are both nutritionally effective and ecologically responsible. This study contributes to the theoretical understanding of sustainable food design, emphasizing that future food systems must align chemical integrity, technological efficiency, and environmental stewardship to achieve long-term global food security.